KOMUNIKASI EFEKTIF ANTARA GURU DAN SISWA SEBAGAI FONDASI UTAMA HASIL BELAJAR SISWA - Rahmah, Husna Aulia; Muthia’h, Farah; Suparmi, Suparmi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Effective communication between teachers and students is a crucial foundation for determining learning outcomes and is integral to the transformative education process. This communication function goes beyond ordinary instruction, serving as a bridge that builds academic understanding and emotional support. Open communication encourages students to ask questions and provide feedback, allowing teachers to adjust their teaching. Meanwhile, empathetic communication creates a psychologically safe classroom environment and teaches interpersonal soft skills. This study used a literature review method, selecting 20 relevant articles from 200 articles found, focusing on publications from 2020 to 2025. The results show that effective communication is vital for building good teacher-student relationships and supporting learning. This communication is characterized by a two-way flow of information, facilitating understanding, and changing attitudes. Its implementation is based on three foundations: seven fundamental elements of communication, five principles of quality assurance (such as clarity and accuracy), and five strategic approaches. Effective communication significantly improves student learning outcomes in cognitive, affective, and psychomotor aspects. It serves as a catalyst in realizing the holistic educational goal of producing a generation that is knowledgeable, skilled, and virtuous. Communication barriers (different perceptions, emotional reactions) can be overcome through an integrated framework of teacher professionalism, including the development of pedagogical competencies, differentiated learning, and a culture of reflection. Thus, investing in improving teachers' educational communication competencies is a strategic step towards creating a generation that is intelligent and has strong character